A photonic biosensor-integrated tissue chip platform for real-time sensing of lung epithelial inflammatory markers. Issue 2 (3rd January 2023) - Cognetti, John S.; Moen, Maya T.; Brewer, Matthew G.; Bryan, Michael R.; Tice, Joshua D.; McGrath, James L.; Miller, Benjamin L.
Abstract : Integration of photonic sensors with tissue chips (TCs; also known as microphysiological systems or organ chips) enables real time monitoring of analytes produced by the TC or passed through a model tissue barrier. Abstract : Tissue chip (TC) devices, also known as microphysiological systems (MPS) or organ chips (OCs or OoCs), seek to mimic human physiology on a small scale. They are intended to improve upon animal models in terms of reproducibility and human relevance, at a lower monetary and ethical cost. Virtually all TC systems are analyzed at an endpoint, leading to widespread recognition that new methods are needed to enable sensing of specific biomolecules in real time, as they are being produced by the cells. To address this need, we incorporated photonic biosensors for inflammatory cytokines into a model TC. Human bronchial epithelial cells seeded in a microfluidic device were stimulated with lipopolysaccharide, and the cytokines secreted in response sensed in real time. Sensing analyte transport through the TC in response to disruption of tissue barrier was also demonstrated. This work demonstrates the first application of photonic sensors to a human TC device, and will enable new applications in drug development and disease modeling.